IMPLICATIONS OF PERCEIVED BEHAVIORAL CONTROL ON ENTREPRENEURIAL INTENTIONS OF INDONESIAN COLLEGE STUDENTS: SELF-EFFICACY AS A MEDIATOR - Astuti, Tri; Damayanti, Desita Dyah; Purnamasari, Desti; Sennang, Indo (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2025)
Entrepreneurial intention needs to be considered by the Indonesian government when creating entrepreneurs, especially among students who have the potential to become entrepreneurs. Two psychological variables influence entrepreneurial intention in students. This study aims to test the effect of perceived behavioral control on entrepreneurial intention by involving self-efficacy as a mediator variable. This study uses a quantitative method, using Hayes' Process Macro analysis and the Statistical Package for the Social Sciences (SPSS) program. The research subjects involved in this study were 199 active students. This study obtained a BootLLCI value of 0.1576, which is greater than BootULCI 0.418, which shows that self-efficacy does have a significant influence as a mediator between perceived behavioral control and entrepreneurial intention in students. This study is expected to provide a deeper understanding to researchers and practitioners, especially in educational institutions, about the development of entrepreneurial intention by considering psychological factors in students.